2000
DOI: 10.1021/ci000442u
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Based Quantitative Structural Property Relations (QSPRs) for Predicting Boiling Points of Aliphatic Hydrocarbons

Abstract: Quantitative structural property relations (QSPRs) for boiling points of aliphatic hydrocarbons were derived using a back-propagation neural network and a modified Fuzzy ARTMAP architecture. With the backpropagation model, the selected molecular descriptors were capable of distinguishing between diastereomers. The QSPRs were obtained from four valance molecular connectivity indices ( 1 v , 2 v , 3 v , 4 v ), a second-order Kappa shape index ( 2 κ), dipole moment, and molecular weight. The inclusion of dipole m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 29 publications
1
54
1
Order By: Relevance
“…The advantage of NNs, over classical regression analysis methods, is their inherent ability to incorporate nonlinear relationships between chemical structural parameters and physicochemical properties. [16][17][18][19][20][21] Neural network/QSPR models for estimating the Henry's Law constant for a data set of 357 organic compounds (-7.08 e logH e 2.32) have been recently reported by English and Carroll (2001). 16 The above authors reported QSPRs based on 12-4-1 and 10-3-1 backpropagation neural network architectures (trained using 303 compounds) that performed with absolute errors of 0.237 and 0.281 logH units for the test set (54 compounds), respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of NNs, over classical regression analysis methods, is their inherent ability to incorporate nonlinear relationships between chemical structural parameters and physicochemical properties. [16][17][18][19][20][21] Neural network/QSPR models for estimating the Henry's Law constant for a data set of 357 organic compounds (-7.08 e logH e 2.32) have been recently reported by English and Carroll (2001). 16 The above authors reported QSPRs based on 12-4-1 and 10-3-1 backpropagation neural network architectures (trained using 303 compounds) that performed with absolute errors of 0.237 and 0.281 logH units for the test set (54 compounds), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, neural network-based QSPR models that are based on the cognitive classifier fuzzy ARTMAP have been proposed for the estimation of boiling temperature, 18,19 critical properties, 19 aqueous solubility, 20 and octanol-water partition coefficients 21 of organics. The approach was shown to be superior to the popular back-propagation neural network approach as well as other statistical QSPR correlations reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have modeled the normal boiling point of hydrocarbons. Predictive neural network models have been published for alkanes [86,87], alkenes [88] and for diverse hydrocarbons [89]. As expected, the models typically show good fitting and prediction statistics with less than ten simple descriptors.…”
Section: Quantitative Structure-activity Relationships (Qsar) and Quamentioning
confidence: 55%
“…However, it is not suitable when pattern recognition or feature extraction capabilities are desired because relationships between variables in such networks are embedded within the weights in a distributed form (Bishop, 1995;Hecht-Nielsen, 1995;Hertz et al, 1991). In difficult problems involving pattern recognition, such as those found in the development of QSPRs for data sets of heterogeneous compound classes, it is advantageous to use neural network classifiers, as shown in a number of recent studies (Espinosa et al, 2000(Espinosa et al, , 2001b(Espinosa et al, , 2002Yaffe et al, 2001Yaffe et al, , 2003 on QSPR development.…”
Section: Fuzzy Art and Fuzzy Artmapmentioning
confidence: 99%
“…Backpropagation neural networks have recently emerged as an alternative for the development of QSPRs and quantitative structure-activity relationships (QSARs) to predict physicochemical properties and biological activities, respectively (Bünz et al, 1998;Chow et al, 1995;Egolf and Jurs, 1993;Espinosa et al, 2000Espinosa et al, , 2001aGakh et al, 1994;Hall and Story, 1996;Mitchell and Jurs, 1998;Simamoea et al, 1993;Stanton and Jurs, 1990;Stanton et al, 1991;Viswanadhan et al, 2001;Yaffe et al, 2001Yaffe et al, , 2003. This alternative modeling strategy for QSPR development yields significantly higher prediction accuracy compared to that of traditional regressionbased correlations.…”
Section: Introductionmentioning
confidence: 99%